2001
DOI: 10.1002/ijc.1306
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multidrug-resistance P-glycoprotein (MDR1) in human brain tumors

Abstract: Multidrug resistance (MDR) is associated with the expression of P-glycoprotein (P-gp), an ATP-dependent transporter which expels anti-cancer drugs from cells. In the present study, MDR1 P-gp was immunodetected by Western blot analysis in 60 human brain tumors, including meningiomas, schwannomas, low-grade gliomas (astrocytomas, pilocytic astrocytomas) and high-grade gliomas (anaplastic astrocytomas, glioblastomas and anaplastic oligodendrogliomas). Most samples from primary tumors expressed P-gp at the same le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
53
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 34 publications
5
53
0
1
Order By: Relevance
“…The reverse association of MDR1 expression with HSF1 and β-catenin (Wnt pathway) indicated that different signal pathways contributed to the carcinogenesis of FAP and sporadic CRC. The reduced MDR1 gene expression was also found in other cancers such as kidney cancer [33] and brain cancer [34] . Recently, a large number of studies have revealed the association of iNOS expression with various cancers [35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 75%
“…The reverse association of MDR1 expression with HSF1 and β-catenin (Wnt pathway) indicated that different signal pathways contributed to the carcinogenesis of FAP and sporadic CRC. The reduced MDR1 gene expression was also found in other cancers such as kidney cancer [33] and brain cancer [34] . Recently, a large number of studies have revealed the association of iNOS expression with various cancers [35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 75%
“…Demeule et al found that tumor and vasculature P-glycoprotein expression by Western blot in gliomas was similar to that in normal brain tissue, whereas P-glycoprotein levels in brain metastases from lung adenocarcinomas and melanoma were 40% and 5% of that in normal brain tissue, respectively (37). Furthermore, tumor and its neovasculature from concordant primary lung adenocarcinomas and its brain metastases had low and equal P-glycoprotein immunohistochemistry expression, suggesting the P-glycoprotein levels in MBT reflect P-glycoprotein expression in the tissue of origin (37).…”
Section: Discussionmentioning
confidence: 99%
“…Demeule et al found that tumor and vasculature P-glycoprotein expression by Western blot in gliomas was similar to that in normal brain tissue, whereas P-glycoprotein levels in brain metastases from lung adenocarcinomas and melanoma were 40% and 5% of that in normal brain tissue, respectively (37). Furthermore, tumor and its neovasculature from concordant primary lung adenocarcinomas and its brain metastases had low and equal P-glycoprotein immunohistochemistry expression, suggesting the P-glycoprotein levels in MBT reflect P-glycoprotein expression in the tissue of origin (37). Together, findings suggest significantly decreased P-glycoprotein immunohistochemistry expression in MBT and its neovasculature compared with PBT (36,37) and suggest that the BBB-MDR phenotype in PBT is mediated to a minor degree by tumor cells and predominantly at the level of tumor BBB vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations